Autism spectrum disorder screening in primary care - Gura, Georgette F; Champagne, Mary T; Blood-Siegfried, Jane E (Journal of developmental and behavioral pediatrics, 2011)
One in 110 children in the United States has autism spectrum disorder (ASD). Early identification and early intervention have been shown to improve outcomes for children with ASD. Although recommended, routine ASD screening at 18 and 24 months of age has not been widely adopted in practice. This quality improvement study examined whether a private primary care practice could overcome screening barriers and implement the recommended universal ASD screening practice using the Modified Checklist for Autism in Toddlers™. Guided by the Diffusion of Innovations evidence-based conceptual model, a practice change using the Modified Checklist for Autism in Toddlers™ was developed. A retrospective chart review of 99 subjects was done to evaluate screening fidelity and cost. An overall screening fidelity of 91% was achieved over a 7-month period. The cost of screening to the practice averaged $22.78 per month. This was offset by an average of $38.76 of revenue per month. These findings suggest that low-cost universal screening can be implemented in primary care when addressed from an organizational perspective.